The role of conservative versus innovative nesting behavior on the 25‐year population expansion of an avian predator. Issue 12 (4th May 2017) - Dias, Andreia; Palma, Luís; Carvalho, Filipe; Neto, Dora; Real, Joan; Beja, Pedro
Abstract: Species ranges often change in relation to multiple environmental and demographic factors. Innovative behaviors may affect these changes by facilitating the use of novel habitats, although this idea has been little explored. Here, we investigate the importance of behavior during range change, using a 25‐year population expansion of Bonelli's eagle in southern Portugal. This unique population is almost exclusively tree nesting, while all other populations in western Europe are predominantly cliff nesting. During 1991–2014, we surveyed nest sites and estimated the year when each breeding territory was established. We approximated the boundaries of 84 territories using Dirichlet tessellation and mapped topography, land cover, and the density of human infrastructures in buffers (250, 500, and 1, 000 m) around nest and random sites. We then compared environmental conditions at matching nest and random sites within territories using conditional logistic regression, and used quantile regression to estimate trends in nesting habitats in relation to the year of territory establishment. Most nests (>85%, n = 197) were in eucalypts, maritime pines, and cork oaks. Nest sites were farther from the nests of neighboring territories than random points, and they were in areas with higher terrain roughness, lower cover by agricultural and built‐up areas, and lower road and powerline densities. Nesting habitat selection varied little with year of territory establishment, although nesting in eucalypts increased, while cliff nesting and cork oak nesting, and terrain roughness declined. Our results suggest that the observed expansion of Bonelli's eagles was facilitated by the tree nesting behavior, which allowed the colonization of areas without cliffs. However, all but a very few breeding pairs settled in habitats comparable to those of the initial population nucleus, suggesting that after an initial trigger possibly facilitated by tree nesting, the habitat selection remained largely conservative. Overall, our study supports recent calls to incorporate information on behavior for understanding and predicting species range shifts. Abstract : Bonelli's eagles in southern Portugal nest in trees, while all other populations in western Europe are cliff nesters. During a 25‐year period of expansion, Bonelli's eagles from this population retained the tree nesting behavior and consistently selected nesting sites in rough terrain, far from sources of human disturbance, and far from the nests of neighboring pairs. We suggest that tree nesting behavior facilitated the expansion of this Bonelli's eagle population, highlighting the importance of behavioral diversity for species conservation.